Women’s Health and the Affordable Care Act: High Hopes Versus Harsh Realities? - Hall, Kelli Stidham (American Public Health Association, 2014)
Our population-based survey of 1078 randomly sampled US women, aged 18 to 55 years, sought to characterize their understanding of and attitudes toward the Affordable Care Act (ACA). Most women, especially socially disadvantaged groups, had negative or uncertain attitudes toward the ACA and limited understanding of its health benefits, including its relevance for their own health service coverage and utilization. Our findings are important for continued research, policy, and practice, with implications for whether, when, and how improved coverage will translate to improved access and outcomes for US women.